Challenges of the Supported Teaching in Schools (Sts) Programme: A Case of E.P College of Education Amedzofe. - Bobi, Comfort; Mawutor, Courage Jerry Worlanyo; Ahiavi, Martin (Journal of Education and Practice, 2023)
Purpose: To identify challenges in the Supported Teaching in School Program at E.P. College of Education Amedzofe, Ghana. Methodology: A case study design was used, involving 329 mentees, 113 mentors, and 41 tutors from the college. Data collection was done through Google Forms and analyzed using the Statistical Package for the Social Sciences. Findings: Key issues included insufficient motivation for tutors and mentors, problematic transportation for mentees to attachment schools, and a lack of adequate teaching resources at these schools. Unique Contribution to theory, policy and practice: The study recommends that the Ministry of Education allocate sufficient resources, including teachers' manuals and logistics, for the program's success. It recommends the college engage with stakeholders and NGOs for better motivation of tutors and mentors. Additionally, coordinating transportation solutions for mentees is suggested. These insights offer practical strategies for enhancing teacher training programs and inform policy decisions in educational settings